An Analysis of Studets’ Ability in Writing Persuasive Text - Maulidya Mayang Widhari; Azhary Tambusai; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
This research aims was to determine (1) the students’ ability in writing persuasive text and (2) to find out what factors affect students' ability to write persuasive text. This research is descriptive qualitative. In this research the sample was taken by means of cluster random sampling as many as 25 students. Data were collected through tests in the form of persuasive texts written by students and then through analytical procedures according to the rubric of assessment aspects and through non-test, namely questionnaire. Then the data collected will be presented in the form of a description. Based on the results of the research, it is known that the students' ability in writing persuasive text is good (capable). It is proven that the average value obtained reaches 79.5 and the number of students who are less able to write persuasive text well and get a score below the KKM is 24% of students. This means that students who have been able to reach the KKM are 76% of students with good interpretations.